Harmonic image reconstruction assisted by a nonlinear metmaterial surface - Wang, Zhiyu (2015)
We experimentally demonstrate a microwave far-field image reconstruction modality with the transverse resolution exceeding the diffraction limit by using a single layer of highly nonlinear metamaterial. The harmonic fields of the nonlinear metamaterial surface allow the far-field propagation of wave fronts with spatial frequencies several times higher than that of the fundamental field. Near-field images can thus be mathematically recovered from the far-field patterns of the harmonic fields.